Educational choices in Ethiopia - Pereznieto, P; Jones, N (2006)
Ethiopia has one of the lowest primary school enrolment rates and one of the highest illiteracy rates in the world. These rates are significantly lower than those of other similarly low-income countries. There are concerns that education quality is falling due to insufficient spending to provide more teachers and textbooks and reform the curriculum. Other key problems include disparities between regions, between boys and girls, and between rural and urban areas. It remains uncertain whether Ethiopia will attain the second Millennium Development Goal of universal primary education by 2015. Young Lives research in Ethiopia addresses questions of educational enrolment, and considers the out-of-school factors that influence it. Most research to date has focussed on the supply of educational services, while largely overlooking out-of-school factors. This policy brief examines demand for school, shortcomings in the education sector and factors such as household size, child work, economic shocks and school accessibility. The authors consider the policy implications of this research relating to educational sector reforms, financing reforms, and cross-sectoral reforms, such as those addressing child labour and gender inequality.